An Analysis of Follow‐On Development in New Drug Classes, January 1986–June 2018. Issue 5 (26th July 2019) - Lanthier, Michael L.; Kerr, Kirk W.; Miller, Kathleen L.
Abstract : Follow‐on drugs—new medicines approved within an established drug class—provide incremental treatment improvements, additional choices for clinicians and patients, and potential price competition. We examine the timing, quantity, and product characteristics of within‐class drug approvals for new drug classes approved by the US Food and Drug Administration since January 1986. We find that nearly two‐thirds of first‐in‐class drugs do not face a subsequent follow‐on product. Follow‐on innovation within a drug class was more common and occurred more rapidly in the 1990s than during the 2000s. We also find that fewer drug classes have multiple competitors entering the market during the 2000s. First‐in‐class drugs treating rare disorders experienced lower rates of follow‐on entry than drugs treating common medical conditions. The decreased pace of follow‐on development likely results from greater industry focus on rare diseases and increasing reimbursement pressure on products lacking clear advantages over existing products.